2015
DOI: 10.1161/strokeaha.114.008387
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends in Incidence and Case Fatality of Ischemic Stroke

Abstract: Background and Purpose-Ischemic stroke incidence has declined in industrialized countries the last decades, with possible exception for the youngest age groups. We estimated age-and sex-specific trends in incidence and case fatality of firstever ischemic stroke between 1977 and 2010 in a Norwegian municipality. Methods-Age-adjusted time trends in incidence from 1977 to 2010 were estimated by fractional polynomial and Poisson regression, and case fatality by logistic regression in 36 575 participants of the pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 25 publications
2
36
0
2
Order By: Relevance
“…The observed decline in stroke incidence in our study was confined to IS, whereas the incidence of hemorrhagic stroke remained unchanged. Similarly, a study from Tromsø, Norway, reported a 24% decrease in first-ever IS incidence between 1995 and 2010 [23]. The absolute number of incident first-ever stroke cases decreased by almost 10% in our study area between 2001–2002 and 2015–2016 despite an increase in population size with 18%, as well as a 1% increase in the proportion of individuals ≥75 years.…”
Section: Discussionsupporting
confidence: 69%
“…The observed decline in stroke incidence in our study was confined to IS, whereas the incidence of hemorrhagic stroke remained unchanged. Similarly, a study from Tromsø, Norway, reported a 24% decrease in first-ever IS incidence between 1995 and 2010 [23]. The absolute number of incident first-ever stroke cases decreased by almost 10% in our study area between 2001–2002 and 2015–2016 despite an increase in population size with 18%, as well as a 1% increase in the proportion of individuals ≥75 years.…”
Section: Discussionsupporting
confidence: 69%
“…Mortality after stroke in the ARIC communities declined over time by 10% to 20%, particularly among those aged <65 years. Similar trends have been observed in men (but not women) in the Framingham study 32 in Minneapolis-St. Paul 33 ; in Tromsø, Norway 34 ; and in Auckland, New Zealand, 35 but not observed in Oxfordshire, United Kingdom 36 or Perth, Australia. 37 Even greater decreases in mortality because of stroke were observed in Denmark (45% reduction from 1994-1998 to 2009-2011)…”
Section: Ischemic Strokementioning
confidence: 89%
“…22 Ischemic stroke incidence declined during 1995 to 2010 and case-fatality declined in men but not in women. 23 Intracerebral hemorrhage incidence showed no time trends during 1995 to 2010. 24 CVD risk factor reduction, mainly through decrease in total cholesterol, blood pressure, and prevalence of smoking, explain more than half of the reduction in coronary heart disease mortality observed in Norway's neighboring countries, Finland 25 and Sweden, 26 from the 1980s and onwards.…”
Section: The Blood Pressure Distributionmentioning
confidence: 98%